Distributional patterns of aquatic Oligochaeta communities (Annelida: Clitellata) in running waters in Serbia - Atanacković, Ana D.; Zorić, Katarina S.; Tomović, Jelena M.; Vasiljević, Božica M.; Paunović, Momir M. (Archives of Biological Sciences, 2020)
Paper description: Aquatic oligochaetes are an important macroinvertebrate group in Serbian freshwaters. They were the subject of sporadic hydrobiological studies in the past, but the complete fauna of the oligochaetes has not been published. Literature data about species distribution combined with complete updated checklists of oligochaeta communities confirm their high biological diversity in Serbia and report 12 new species. Community composition was analyzed to assess the correlation with abiotic typology descriptors. This work confirms the indicator value of the oligochaeta and their “ecological footprint” for saprobic/organic contamination. Abstract: The study of aquatic Oligochaeta in freshwaters in Serbia contributes to the oligochaete fauna inventory of the Balkans. Based on our results and literature review, 97 species (45 genera from 8 families) are listed in the running waters of Serbia. From the list of 61 species recorded during our investigation, 12 were noted for the first time. The ecological analysis of Oligochaeta communities showed the largest participation of potamal and rhithral species. As regards current preferences, rheolimnophilous species predominated, and with respect to feeding type, collectors prevailed. Most of the species are tolerant to moderate and high organic load. According to microhabitat preferences, three types of rivers stood out, as follows: (1) pelophilous (dominance of L. hoffmeisteri); (2) psammophilous (dominance of S. heringianus); (3) phytophilous (dominance of N. bretscheri). Analyses of the relation to different types of waterbodies showed regularity in the distribution of oligochaetes, with a higher species richness in main watercourses (types 1 and 2), and a lower species richness in tributaries (types 3, 4 and 6). According to the dominant taxa, the running waters of Serbia can be classified into four groups which are characterized by the prevalence of naidids (naidins and tubificins), enchytraeids and lumbriculids. Our results show that community composition is a good indicator of the horizontal distribution of Oligochaeta. https://doi.org/10.2298/ABS200303030A Received: March 3, 2020; Revised: June 26, 2020; Accepted: July 30, 2020; Published online: July 15, 2020 How to cite this article: Atanacković AD, Zorić KS, Tomović JM, Vasiljević BM, PaunovićMM. Distributional patterns of aquatic Oligochaeta communities (Annelida: Clitellata) in running waters in Serbia. Arch Biol Sci. 2020;72(3):359-72.